Promosi Sebagai Upaya Pengembangan Usaha (UMKM) Melalui Sosial Media - Nadya, Nadya Al Nafturahma (Universitas Dehasen Bengkulu, 2024)
Micro, Small and Medium Enterprises (MSMEs) are part of the independent Indonesian economy and have great potential to improve people's welfare. Micro, Small and Medium Enterprises (MSMEs) also play a role in increasing technological development, creating new markets, increasing employment opportunities and producing better micro, small and medium enterprises. In addition, MSMEs also have obstacles in their development, one of which is the difficulty of selling or marketing the products produced. The development of technology has brought great changes and is very useful, including for business development, making it easy to promote product sales through various market place platforms on social media. In this way, MSME players get many benefits, can be done anywhere and anytime regardless of space and time, and broad coverage. Therefore, it is necessary to have knowledge about the use of social media as an effort to develop existing businesses. Based on these problems, we aim to help business owners by providing education about promotion as a business development effort.